Dihydrotestosterone reduces neuroinflammation in spinal cord injury through NF-κB and MAPK pathway: Dihydrotestosterone reduces neuroinflammation in SCI - Wei, Jiarui; Li, Tao; Lin, Shengyuan; Zhang, Bin; Li, Xing (Cellular and Molecular Biology, 2024)
Neuroinflammation induced by microglia following spinal cord injury (SCI) leads to secondary neurologic injury. Androgens including testosterone and dihydrotestosterone (DHT) show as endogenous neuroprotective factors against multiple neurologic diseases, while their therapeutic role in SCI-induced neuroinflammation and underlying mechanism remains elusive. In the study, we aimed to investigate the role of DHT against microglia-induced neuroinflammation in SCI and evaluate its protective treatment. BV2 cells were activated by neuroinflammation via LPS in vitro. Adult male C57BL/6 mice were used to establish the SCI model. BV2 cells and SCI mice were administrated DHT. Microglia activation, pro-inflammatory factors, p38 and p65 phosphorylation, glial scar, fibrotic scar, histology, and locomotor function recovery were measured, respectively. We demonstrated that DHT administration attenuates neuroinflammation in microglia through inhibition of p38 and p65 pathways. Moreover, DHT reduces microglia and astrocyte accumulation, cord fibrosis and histologic damage. Besides, DHT ameliorates locomotor functional recovery after SCI. DHT is verified to play a neuroprotective role in SCI, which fights against neuroinflammation by inhibition of p38 and p65 pathways. Therefore, Mel is defined as a promising factor in protecting neural tissue after SCI.